Between sign and screen. Two cases of 'liminary' anthologies in the 2000s (Configurazioni. Research on contemporary poetry, 2023)
This essay will present some reflections about the evolution of anthology as a form and as a literary genre over the last two decades. After a historical and theoretical overview, two specific phenomena – typological hybridization and intermedial hybridization – will be analyzed, through two highly representative case studies: 5x5. Poesia italiana dal nuovo millennio (2019), curated by Ivan Schiavone, and Asemic writing. Contributi teorici (2018), by Francesco Aprile and Cristiano Caggiula.
Keywords: Poetry Anthology; XXI Century Italian Poetry; Digital Age; Intermediality; Asemic Writing